Systematic revision of Acanthodactylus busacki (Squamata: Lacertidae) with a description of a new species from Morocco - Tamar, Karin; Geniez, Philippe; Brito, José C.; Crochet, Pierre-André (Zootaxa, 2017)
Recent molecular phylogenies of the Acanthodactylus pardalis species-group have revealed a deep genetic divergence within the nominal species A. busacki from north-west Africa. The species is phylogenetically separated into northern and southern lineages, which correspond to a previously observed morphological differentiation between the northern and southern populations of this species. Based on morphological comparisons of the type material and location of the type locality, the nomen Acanthodactylus busacki Salvador, 1982 is assigned here to the southern lineage, known from the northern Saharan Atlantic coastal desert. The northern lineage, described here as Acanthodactylus margaritae sp. nov., is prominently characterized by weakly keeled dorsal scales and a characteristic colour pattern. The new species is endemic to Morocco and confined to arid and semi-arid bioclimatic areas between the High Atlas and Anti-Atlas Mountains, from around Tamri in the north to Tiznit in the south and the Souss valley in the east.